Environmental and techno-economic considerations on biodiesel production from waste frying oil in São Paulo city. (10th May 2018) - Silva Filho, Silvério Catureba da; Miranda, Amanda Carvalho; Silva, Thadeu Alfredo Farias; Calarge, Felipe Araújo; Souza, Roberto Rodrigues de; Santana, José Carlos Curvelo; Tambourgi, Elias Basile
Abstract: Biodiesel is a renewable and biodegradable fuel that reduces the greenhouse gas emissions and global warming. However, the use of food oils in biodiesel production is severely criticised because its impacts on food prices, increase in crop area and deforestation. Thus, the production of biodiesel from non-food sources should be encouraged. This study was aimed at producing biodiesel from waste frying oil from residences and restaurants in an economically and environment-friendly manner. Therefore, a kinetic study of the transesterification reaction was carried out for each frying oil source. Energy and greenhouse gas emission efficiency values were measured in a diesel oil engine. Managers and residents answered some questions for evaluation of the environmental and economic sustainability of the city of São Paulo. The results of measurements showed that the biodiesel kinetics were zero order relative to frying oil concentration, leading to a 90.10% yield, and biodiesel physicochemical properties were in compliance with the Brazilian standards. For blends up to 30%, net power of each biodiesel was equal to that of diesel oil, but the reduction in greenhouse gas emissions were reduced by 33% compared to diesel oil. The statistical survey revealed that the city of São Paulo has a production potential of more than 8800 m 3 per month, which can generate savings of US$ 5, 000, 000 per month and an additional profit of US$ 7, 000, 000 per month owing to the sale of excess biodiesel, glycerin, and carbon credits. Thus, this work shows how to make the city more sustainable and contributes to the improvement of its image. Graphical abstract: Image 1 Highlights: The issue confirms the reduction of greenhouse gas emissions by use of biodiesel. Waste frying oil is transformed in quality biodiesel with high energy potential. It uses environmental cost accounting in producing of waste frying oil biodiesel. The economic and environmental viabilities of biodiesel production is proven. It is a way to reduce the criticism on use of food oil in biodiesel production.